A nitrogen-doped carbon composite material with high loading of transition metal single atoms, preparation method and application thereof

By using small nitrogen-containing molecules and zinc ions in the aqueous solution of the surfactant, the problem of low loading of single atom catalyst was solved, and a high-load nitrogen-doped carbon composite material was prepared for ORR electrocatalysts and had high catalytic activity.

CN115347199BActive Publication Date: 2025-04-01BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210998866.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-19
Publication Date
2025-04-01
Estimated Expiration
2042-08-19

AI Technical Summary

Technical Problem

Due to the high surface energy of existing single-atom catalysts, the loading of metal atoms is low and the mass activity is limited, making it difficult to apply in industrial production.

Method used

By using the first nitrogen-containing small molecule and the second nitrogen-containing small molecule in the aqueous solution of the surfactant, uniform dispersion and high loading of the transition metal M ions are achieved.

Benefits of technology

The preparation of nitrogen-doped carbon composite materials with high loading of transition metal single atoms has been realized, which improves the intrinsic activity of the catalyst and the number of active sites. It is suitable for oxygen reduction reaction (ORR) electrocatalysts and has high catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115347199B_ABST
    Figure CN115347199B_ABST
Patent Text Reader

Abstract

The present invention relates to a nitrogen-doped carbon composite material with a high load of transition metal single atoms, a preparation method and an application thereof, and belongs to the field of photocatalyst technology. The composite material uses a nitrogen-doped carbon material as a carrier, and a transition metal single atom is loaded on the carrier, and one transition metal single atom coordinates with four nitrogen atoms to form M-N4, and the transition metal M is Fe, Co, Ni, Cu or Mn. The method is to add a soluble transition metal M salt solution and a soluble zinc salt solution after mixing a surfactant, a first nitrogen-containing small molecule and a second nitrogen-containing small molecule, stirring and drying to obtain a powder material, and pyrolyzing to obtain the composite material. The composite material is used as an ORR electrocatalyst and has a high catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nitrogen-doped carbon composite material with high-load transition metal single atoms, a preparation method and application thereof, and belongs to the technical field of electrocatalysts. Background Art

[0002] Oxygen reduction reaction (ORR) is an important half-reaction in metal-air batteries, fuel cells and other fields. Currently, common ORR electrocatalysts include precious metal Pt-based catalysts, heteroatom-doped carbon, nitrogen-doped carbon and carbon-coated Fe3C complexes, single-atom catalysts, etc. Due to the scarcity, high cost, poor stability and other problems of precious metals, the development of cheap and efficient non-precious metal catalysts (such as Fe, Co, etc. or non-metallic catalyst carbon) that can replace precious metal catalysts is an important research direction in the field of energy technology research, and plays an important role in solving some key technical problems and cost problems in the field of energy storage and conversion.

[0003] Single-atom catalysts have attracted extensive attention due to their high atomic utilization, high selectivity, adjustable coordination environment and excellent catalytic activity. Generally speaking, the atomically dispersed metal active centers of metal-nitrogen-carbon (MNC, M is Fe, Co, Ni, Cu, Zn or Mn, etc.) catalysts have a clear M-N4 coordination configuration, which provides convenient conditions for the performance of electrocatalytic performance and the regulation of its coordination structure. Among the many MNC catalysts, Fe-NC catalysts with Fe-N4 configuration have more suitable binding energy for oxygen-containing intermediates in the ORR process, which makes them show very excellent ORR catalytic activity and stability, and are considered to be materials with the potential to replace precious metal platinum catalysts [Angew. Chem. 2017, 129, 13988–13992; Adv. Mater. 2018, 30, 1803220; Adv. Mater. 2020, 32, 2004900]. Improving the intrinsic activity of the catalyst and the number of active sites are two main ways to improve the activity of the catalyst [Science, 2017, 355, eaad4998]. The design of the carrier material plays an important role in regulating the loading and intrinsic activity of the catalyst. Heteroatom-doped carbon materials, especially nitrogen-doped carbon, are currently commonly used carrier materials for single-atom catalysts. By selecting suitable materials containing carbon and nitrogen element precursors, favorable conditions can be provided for the loading and dispersion of metal active centers. During the high-temperature pyrolysis process, the precursor complex will be converted into nitrogen-doped carbon under high temperature conditions. The relatively strong electronegativity of nitrogen can anchor metal atoms on the nitrogen-doped carbon carrier, and the presence of metal elements can increase the degree of graphitization of the carbon material formed during the pyrolysis process, thereby improving the conductivity of the catalyst. The bamboo-shaped carbon nanotube / Fe3C nanoparticle composite catalyst prepared by surfactant P123, melamine and ferric nitrate, the metal in the precursor composite will agglomerate and form particles during high-temperature pyrolysis, and it is difficult to obtain a uniformly dispersed single-atom catalyst [J.Am.Chem.Soc.2015,137,1436-1439]. When the metal organic framework structure -NH2-MIL(Fe)- is used as a precursor material, phytic acid and melamine are used to regulate and prepare the metal single-atom catalyst, the obtained structure is a composite of Fe-NC catalyst and iron phosphide FeP [J.ColloidInterface Sci.,583(2021)371–375]. The above examples prove that the selection of the precursor of the synthetic catalyst and the ratio of the amount of the precursor have a very significant effect on the morphology and structure of the final catalyst and the existence form of the metal element.At present, single-atom catalysts have low metal atom loading due to high surface energy and limited mass activity. The loading of metal centers in most catalysts is generally low, with most Ni single-atom catalysts loading only 1wt%, and Fe loading less than 2wt% [Nature Nanotech 2018, 13, 411–417; Nat. Nanotechnol. 2022, 17, 174–181]. Low loading is not conducive to the application of catalysts in actual industrial production, so the development of high-loading, high-stability single-atom catalysts is also a major key issue in the field of catalysis. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a nitrogen-doped carbon composite material with high transition metal single atom loading, a preparation method and its application. In the present invention, in an aqueous solution of a surfactant, hydrogen bonds interact with each other between the first nitrogen-containing small molecule and the second nitrogen-containing small molecule to form a nanosheet structure, and the abundant nitrogen-containing sites can coordinate and bond with the transition metal M ions to form a coordination complex. The presence of Zn ions can compete with the transition metal M ions for coordination, so that the M ions are more evenly dispersed in the coordination complex, and the target metal ions are prevented from aggregating during the pyrolysis process, and then pyrolyzed to form an M-N4 structure, while removing Zn, to prepare a nitrogen-doped carbon composite material with high transition metal loading and single-atom molecules.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing a nitrogen-doped carbon composite material with high loading of transition metal single atoms, the method comprising the following steps:

[0007] (1) dispersing a surfactant in water with a purity higher than that of deionized water, adding a first nitrogen-containing small molecule and a second nitrogen-containing small molecule, stirring and dispersing the mixture uniformly to obtain a premix; wherein the first nitrogen-containing small molecule is melamine or dicyandiamide; and the second nitrogen-containing small molecule is cyanuric acid;

[0008] (2) under stirring, dropwise adding a soluble transition metal M salt solution and a soluble zinc salt solution to the premix, continuing stirring for 5 h to 10 h to obtain a mixture, and drying to obtain a powder material; wherein the transition metal is one or more of Fe, Co, Ni, Cu and Mn; and the molar ratio of the transition metal M salt, the zinc salt and the first nitrogen-containing small molecule is 0.025 to 0.25:0.036 to 0.36:4 to 8;

[0009] (3) Under the protection of protective gas, the powder material is kept at 240° C. to 300° C. for 1 h to 2 h, and then the temperature is increased to 900° C. to 1100° C. and kept for 2 h to 5 h. After the insulation is completed, a nitrogen-doped carbon composite material with a high load of transition metal single atoms is obtained.

[0010] Preferably, in step (1), the surfactant is poloxamer F127, polyvinyl pyrrolidone or polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).

[0011] Preferably, in step (1), the mass ratio of the surfactant, the first nitrogen-containing small molecule and the second nitrogen-containing small molecule is 0.3-1.0:0.6-1.2:0.6-1.2.

[0012] Preferably, in step (2), a soluble transition metal M salt solution is first added dropwise, and then a soluble zinc salt solution is added dropwise.

[0013] Preferably, in step (2), the soluble transition metal M salt is one or more of ferric nitrate, copper sulfate, copper nitrate, nickel sulfate, nickel nitrate, manganese nitrate and cobalt nitrate; and the soluble zinc salt is zinc nitrate.

[0014] Preferably, in step (2), during drying, the mixture is first cooled in liquid nitrogen and then freeze-dried or dried at 110° C. to 120° C. for 6 h to 10 h.

[0015] Preferably, the heating rate in step (3) is 2°C / min to 5°C / min.

[0016] A nitrogen-doped carbon composite material with a high load of transition metal single atoms as described in the present invention, wherein the composite material uses a nitrogen-doped carbon material as a carrier, and the carrier is loaded with transition metal single atoms, one transition metal single atom is coordinated with four nitrogen atoms to form M-N4, and the transition metal M is Fe, Co, Ni, Cu or Mn.

[0017] Preferably, based on the total mass of the composite material being 100%, the loading amount of the transition metal single atom is 4% to 10.5%.

[0018] An application of the nitrogen-doped carbon composite material with high transition metal single atom loading according to the present invention, wherein the composite material is used as an ORR electrocatalyst.

[0019] Beneficial Effects

[0020] The present invention provides a method for preparing a nitrogen-doped carbon composite material with a high load of transition metal single atoms. The method realizes uniform dispersion of metal ions in transition metal M salts and zinc salts based on the uniform dispersion and coordination of a surfactant, a first nitrogen-containing small molecule and a second nitrogen-containing small molecule on a metal precursor, and the coordination of transition metal M atoms is made more uniform through the bonding action of organic molecules and the competitive coordination action of zinc ions. In addition, Zn atoms are removed due to volatilization during high-temperature pyrolysis, thereby realizing maximum single-atom dispersion loading of transition metal M atoms and effectively increasing the loading amount of transition metal M atoms.

[0021] In the method, the surfactant is poloxamer F127, polyvinyl pyrrolidone or P123; the first nitrogen-containing small molecule is melamine or dicyandiamide; the second nitrogen-containing small molecule is cyanuric acid, and under the action of the surfactant, the first nitrogen-containing small molecule and the second nitrogen-containing small molecule form a complex through polymerization, and the complex contains abundant nitrogen-containing sites that can coordinate with the transition metal M atom, thereby achieving uniform coordination of the metal element.

[0022] In the method, by controlling the dropwise addition order of the soluble transition metal M salt solution and the soluble zinc salt solution, the metal precursor can be quickly and evenly dispersed in a short time. The competitive coordination between zinc ions and target metal atoms on the composite precursor is utilized to make the target metal element M more evenly dispersed on the carrier, and the agglomeration of metal atoms into particles in the subsequent pyrolysis process is avoided as much as possible.

[0023] In the method, the pyrolysis process adopts a two-step staged heating. First, the pretreatment in the first stage can remove a small amount of unstable components to facilitate the subsequent high-temperature pyrolysis process. The high-temperature pyrolysis in the second stage can convert the precursor material into nitrogen-doped carbon while obtaining a single-atom catalyst with an M-N4 configuration. Under such high-temperature conditions, the volatilization and removal of metal Zn can also be ensured.

[0024] The present invention provides a nitrogen-doped carbon composite material with a high load of transition metal single atoms. The composite material uses a nitrogen-doped carbon material as a carrier, and the carrier is loaded with transition metal single atoms. One transition metal single atom is coordinated with four nitrogen atoms to form M-N4, and the transition metal M is Fe, Co, Ni, Cu or Mn; and the loading amount of the transition metal M atoms is as high as more than 4%.

[0025] The present invention provides an application of a nitrogen-doped carbon composite material with a high load of transition metal single atoms. The composite material is used as an ORR electrocatalyst and has high catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart of the preparation method.

[0027] Figure 2 The X-ray diffraction (XRD) patterns of the composite materials described in Examples 1-3.

[0028] Figure 3 This is a transmission electron microscope (TEM) image of the composite material described in Example 1.

[0029] Figure 4 This is the TEM image of the composite material described in Example 2.

[0030] Figure 5 This is the TEM image of the composite material described in Example 3.

[0031] Figure 6 This is the synchrotron radiation fitting result of the composite material described in Example 3.

[0032] Figure 7 This is a transmission electron microscopy image of the composite material corrected for spherical aberration described in Example 3.

[0033] Figure 8 This is the alkaline medium ORR activity curve of the composite material described in Examples 1-3.

[0034] Fig. 9 This is the TEM image of the composite material described in Comparative Example 1. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with specific embodiments.

[0036] In the following examples or comparative examples:

[0037] (1) XRD test: Rigaku MiniFlex 600 desktop X-ray diffractometer (Japan).

[0038] (2) TEM test: HITACHI H-7700 transmission electron microscope.

[0039] (3) High-resolution transmission electron microscopy (HRTEM) test: JEOL JEM-2100F high-resolution transmission electron microscope.

[0040] (4) Inductively coupled plasma optical emission spectroscopy: Japan Shimadzu ICPE-9800 (OES)

[0041] (5) Synchrotron radiation fitting: Beijing Synchrotron Radiation Center 1W1B workstation

[0042] (6) Spherical aberration corrected transmission electron microscope: Titan 80–300 scanning / projection electron microscope

[0043] (7) Alkaline medium ORR activity test: tested on Shanghai Chenhua electrochemical workstation CHI760E.

[0044] Example 1

[0045] (1) Weigh 0.6 g of poloxamer F127, disperse it in 30 mL of ultrapure water, and stir for 30 min until it is evenly dispersed; add 1.0 g of melamine, and stir for 30 min until it is evenly dispersed; then add 1.0 g of cyanuric acid, and stir for 30 min until it is evenly dispersed to obtain a premix;

[0046] (2) under stirring, 0.25 mL of a 200 mg / mL iron nitrate solution and 0.25 mL of a 200 mg / mL zinc nitrate solution were sequentially added dropwise to the premix, and stirring was continued for 10 h to obtain a mixture, the mixture was rapidly cooled in liquid nitrogen, and then freeze-dried in a freeze dryer to obtain a powder material;

[0047] (3) Under the protection of protective gas, the powder material is placed in a tubular furnace, first heated to 240°C and kept warm for 1 hour, then heated to 900°C and kept warm for 2 hours, with a heating rate of 5°C / min during the heating process. After the insulation, a nitrogen-doped carbon composite material with a high load of iron metal single atoms is obtained.

[0048] The XRD test results of the composite material are as follows: Figure 2 As shown in the figure, only the peak of graphite carbon is found at about 26°, and no peaks of other metal phases or impurity phases such as metal carbides are found, which preliminarily proves that no aggregation of metal atoms occurs in the composite material.

[0049] The TEM test results of the composite material are as follows: Figure 3 As shown, combined with the HRTEM results, it can be seen that no metal particles or metal phases are found in the composite material, which further proves that the composite material prepared in this example does not have metal agglomeration.

[0050] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Fe-N4 structure.

[0051] The test results of inductively coupled plasma emission spectroscopy show that the content of Fe in the composite material is 5.01wt%.

[0052] The alkaline oxygen reduction activity polarization curve of the composite material is as follows Figure 8 As shown, the results show that the half-wave potential of the composite material is 0.878 V vs. RHE, showing a high potential for catalytic oxygen reduction.

[0053] Example 2

[0054] (1) Weigh 0.6 g of poloxamer F127, disperse it in 30 mL of ultrapure water, and stir for 30 min until it is evenly dispersed; add 1.0 g of melamine, and stir for 30 min until it is evenly dispersed; then add 1.0 g of cyanuric acid, and stir for 30 min until it is evenly dispersed to obtain a premix;

[0055] (2) under stirring, 0.35 mL of a 200 mg / mL iron nitrate solution and 0.35 mL of a 200 mg / mL zinc nitrate solution were sequentially added dropwise to the premix, and stirring was continued for 10 h to obtain a mixture, the mixture was rapidly cooled in liquid nitrogen, and then freeze-dried in a freeze dryer to obtain a powder material;

[0056] (3) Under the protection of protective gas, the powder material is placed in a tubular furnace, first heated to 300° C. and kept warm for 1 hour, then heated to 950° C. and kept warm for 2 hours. The heating rate during the heating process is 5° C. / min. After the insulation, a nitrogen-doped carbon composite material with a high load of iron metal single atoms is obtained.

[0057] The XRD test results of the composite material are as follows: Figure 2 As shown in the figure, only the peak of graphite carbon is found at about 26°, and no peaks of other metal phases or impurity phases such as metal carbides are found, which preliminarily proves that no aggregation of metal atoms occurs in the composite material.

[0058] The TEM test results of the composite material are as follows: Figure 4 As shown, combined with the HRTEM results, it can be seen that no metal particles or metal phases are found in the composite material, which further proves that the composite material prepared in this example does not have metal agglomeration.

[0059] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Fe-N4 structure.

[0060] The test results of inductively coupled plasma emission spectroscopy show that the content of Fe in the composite material is 6.9wt%.

[0061] The alkaline oxygen reduction activity polarization curve of the composite material is as follows Figure 8 As shown, the results show that the half-wave potential of the composite material is 0.870 V vs. RHE, showing a high potential for catalytic oxygen reduction.

[0062] Example 3

[0063] (1) Weigh 0.6 g of poloxamer F127, disperse it in 30 mL of ultrapure water, and stir for 30 min until it is evenly dispersed; add 1.0 g of melamine, and stir for 30 min until it is evenly dispersed; then add 1.0 g of cyanuric acid, and stir for 30 min until it is evenly dispersed to obtain a premix;

[0064] (2) under stirring, 0.5 mL of a 200 mg / mL iron nitrate solution and 0.5 mL of a 200 mg / mL zinc nitrate solution were sequentially added dropwise to the premix, and stirring was continued for 10 h to obtain a mixture, the mixture was rapidly cooled in liquid nitrogen, and then freeze-dried in a freeze dryer to obtain a powder material;

[0065] (3) Under the protection of protective gas, the powder material is placed in a tubular furnace, first heated to 300° C. and kept warm for 1 hour, then heated to 900° C. and kept warm for 2 hours. The heating rate during the heating process is 5° C. / min. After the insulation, a nitrogen-doped carbon composite material with a high load of iron metal single atoms is obtained.

[0066] The XRD test results of the composite material are as follows: Figure 2 As shown in the figure, only the peak of graphite carbon is found at about 26°, and no peaks of other metal phases or impurity phases such as metal carbides are found, which preliminarily proves that no aggregation of metal atoms occurs in the composite material.

[0067] The TEM test results of the composite material are as follows: Figure 5 As shown, combined with the HRTEM results, it can be seen that no metal particles or metal phases are found in the composite material, which further proves that the composite material prepared in this example does not have metal agglomeration.

[0068] Figure 6 is the Fourier transform diagram and fitting diagram of the EXAFS of Fe K-edge characterized by synchrotron radiation of the composite material, wherein Typical atomic-level Fe-N4-related peaks appeared nearby, but no metal phase peaks were found; this proves that the configuration of the composite material is an atomically dispersed Fe-N4 structure. Figure 7 The spherical aberration electron microscopy image shown more intuitively demonstrates the atomic-level dispersion of Fe atoms in the composite material.

[0069] The test results of inductively coupled plasma emission spectroscopy show that the content of Fe in the composite material is 10.1wt%.

[0070] The alkaline oxygen reduction activity polarization curve of the composite material is as follows Figure 8 As shown, the results show that the half-wave potential of the composite material is 0.886 V vs. RHE, showing a high potential for catalytic oxygen reduction.

[0071] Example 4

[0072] In this embodiment, copper nitrate is used to replace the iron nitrate in Example 3, and the rest is the same as in Example 3.

[0073] The XRD and TEM test results of the composite material show that no agglomeration of metal atoms occurs.

[0074] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Cu-N4 structure.

[0075] The alkaline medium ORR activity test results of the composite material show that the composite material has a high catalytic oxygen reduction ability.

[0076] Example 5

[0077] In this embodiment, nickel nitrate is used to replace the iron nitrate in Example 3, and the rest is the same as Example 3.

[0078] The XRD and TEM test results of the composite material show that no agglomeration of metal atoms occurs.

[0079] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Ni-N4 structure.

[0080] The alkaline medium ORR activity test results of the composite material show that the composite material has a high catalytic oxygen reduction ability.

[0081] Example 6

[0082] In this embodiment, cobalt nitrate is used to replace the iron nitrate in Example 3, and the rest is the same as in Example 3.

[0083] The XRD and TEM test results of the composite material show that no agglomeration of metal atoms occurs.

[0084] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Co-N4 structure.

[0085] The alkaline medium ORR activity test results of the composite material show that the composite material has a high catalytic oxygen reduction ability.

[0086] Example 7

[0087] In this embodiment, the surfactant P123 is used to replace the F127 in Example 3, and the rest is the same as Example 3.

[0088] The XRD and TEM test results of the composite material show that no agglomeration of metal atoms occurs.

[0089] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Fe-N4 structure.

[0090] The alkaline medium ORR activity test results of the composite material show that the composite material has a high catalytic oxygen reduction ability.

[0091] Example 8

[0092] In this embodiment, dicyandiamide is used to replace the melamine in Embodiment 3, and the rest is the same as that in Embodiment 3.

[0093] The XRD and TEM test results of the composite material show that no agglomeration of metal atoms occurs.

[0094] The synchrotron radiation characterization results of the composite material prove that the configuration of the composite material is an atomically dispersed Fe-N4 structure.

[0095] The alkaline medium ORR activity test results of the composite material show that the composite material has a high catalytic oxygen reduction ability.

[0096] Comparative Example 1

[0097] (1) Weigh 0.6 g of poloxamer F127, disperse it in 30 mL of ultrapure water, and stir for 30 min until it is evenly dispersed; add 1.0 g of melamine, and stir for 30 min until it is evenly dispersed; then add 1.0 g of cyanuric acid, and stir for 30 min until it is evenly dispersed to obtain a premix;

[0098] (2) under stirring, 0.6 mL of a 200 mg / mL iron nitrate solution and 0.6 mL of a 200 mg / mL zinc nitrate solution were sequentially added dropwise to the premix, and stirring was continued for 10 h to obtain a mixture, the mixture was rapidly cooled in liquid nitrogen, and then freeze-dried in a freeze dryer to obtain a powder material;

[0099] (3) Under the protection of protective gas, the powder material is placed in a tubular furnace, first heated to 300° C. and kept warm for 1 hour, then heated to 900° C. and kept warm for 2 hours. The heating rate during the heating process is 5° C. / min. After the insulation is completed, an iron-loaded nitrogen-doped carbon composite material is obtained.

[0100] The TEM test results of the composite material are as follows: Fig. 9 As shown, the results indicate that there are particles in the material, and the metal atoms will aggregate and form particles, which is no longer a single atomic distribution structure.

[0101] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing a nitrogen-doped carbon composite material with high loading of transition metal single atoms, characterized in that: The method steps include: (1) dispersing a surfactant, Poloxamer F127, in water with a purity higher than that of deionized water, adding a first nitrogen-containing small molecule and a second nitrogen-containing small molecule, stirring and dispersing the mixture uniformly to obtain a premix; wherein the first nitrogen-containing small molecule is melamine; and the second nitrogen-containing small molecule is cyanuric acid; under the action of the surfactant, the first nitrogen-containing small molecule and the second nitrogen-containing small molecule form a complex through polymerization; (2) under stirring, adding a soluble transition metal M salt solution and a soluble zinc salt solution to the premix, continuing stirring for 10 hours to obtain a mixture, and drying to obtain a powder material; wherein the soluble transition metal M salt is ferric nitrate, the soluble zinc salt is zinc nitrate, and the transition metal is Fe; the molar ratio of the transition metal M salt, the zinc salt and the first nitrogen-containing small molecule is 0.4:0.5:8; (3) Under the protection of protective gas, the powder material is kept at 300° C. for 1 hour, and then the temperature is increased to 900° C. and kept for 2 hours. After the insulation, a nitrogen-doped carbon composite material with a high load of transition metal single atoms is obtained; Wherein, in step (1), the mass ratio of the surfactant, the first nitrogen-containing small molecule, and the second nitrogen-containing small molecule is 0.6:1.0:1.0; In step (2), a soluble transition metal M salt solution is first added dropwise, and then a soluble zinc salt solution is added dropwise; when drying, the mixture is first cooled in liquid nitrogen and then freeze-dried; The composite material uses nitrogen-doped carbon material as a carrier, and the carrier is loaded with transition metal single atoms, one transition metal single atom coordinates with four nitrogen atoms to form M-N4, and the transition metal M is Fe; based on the total mass of the composite material as 100%, the loading amount of the transition metal single atom is 10.1%.

2. The method for preparing a nitrogen-doped carbon composite material with high loading of transition metal single atoms according to claim 1, characterized in that: The heating rate in step (3) is 2°C / min to 5°C / min.

3. A nitrogen-doped carbon composite material with high loading of transition metal single atoms, characterized in that: The composite material is prepared by the preparation method as described in claim 1 or 2, and the composite material uses a nitrogen-doped carbon material as a carrier, and the carrier is loaded with transition metal single atoms, one transition metal single atom is coordinated with four nitrogen atoms to form M-N4, and the transition metal M is Fe; based on the total mass of the composite material as 100%, the loading amount of the transition metal single atom is 10.1%.

4. An application of the nitrogen-doped carbon composite material with high transition metal single atom loading as claimed in claim 3, characterized in that: The composite material is used as an ORR electrocatalyst.

Citation Information

Patent Citations

  • Dual-function oxygen electrode catalyst containing non-noble-metal nanoparticles coated with nitrogen-doped porous carbon layer and preparation method of dual-function oxygen electrode catalyst

    CN106669758A

  • Metal-nitrogen carbon material with atomic-scale dispersed metal as well as preparation method and application thereof

    CN107930672A

  • Controllable synthesis method of monoatomic catalyst with low cost and high loading capacity

    CN111939961A